Knowledge, Practice and Willingness to Participate in Community Health Insurance Scheme among Households in Nigerian Capital City - Aderibigbe S. Adedeji; Aganaba Doyin; Osagbemi G. Kayode; Aderibigbe A. Ayodele (Sudan Journal of Medical Sciences)
Background: Health insurance is a social security system that guarantees the provision of needed health services to persons on the payment of token contributions at regular intervals. The objective of the survey was to determine knowledge, practice and willingness of households in Nigerian Capital City to pay and participate in Community Health Insurance Scheme.